A cost-effective interactive 3D virtual reality system applied to military live firing training. Issue 2 (June 2016) - Bhagat, Kaushal; Liou, Wei-Kai; Chang, Chun-Yen
Abstract The goal of the present study was to develop a cost-effective, man–machine digital interface, to improve students' real-world firing range training, results, and achievement scores. A serious game-based learning environment was developed, integrating invisible laser infrared technology, 1:1 real-scale rifle guns with recoil effects, as well as 3D interactive virtual reality (VR) military training digital information content, to train students in military live firing. To evaluate the effectiveness of the proposed design, students' performance, in terms of their learning achievement and learning motivation, was examined. One hundred and sixty high school students from Taiwan were divided into four individual groups of 40 students each, with one control group and three experimental groups (EG1, EG2, and EG3). The data were analyzed by one-way analysis of variance. The results of this cost-effective 3D VR showed significantly better learning motivation, learning outcomes, and positive impacts on users' actual live firing achievement scores.